PKM PELATIHAN POTENSI KEWIRAUSAHAAN DIWILAYAH TINGGAL PADA MASA PANDEMI COVID-19 - Kiki Ismanti; Nurlaela; Sugeng Haryono (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2021)
The purpose of this service is to foster an entrepreneurial mindset or entrepreneurship. PKK women from Tanjung Barat sub-district rt 011, Rw 002. Jagakarsa sub-district, South Jakarta whose view is Dasawisma. The method we use is to use a Focus Group Discussion (FGD), seeking information directly from the head of the RT and several residents who are members of the dasawisma. After collecting data or information from the community, then we prepare tools and materials to provide the first is to explore the entrepreneurial potential of the community by expressing ideas through business proposals then making a product from a bucket and then filling it with fish and vegetables.